2021
DOI: 10.1136/bcr-2020-240570
|View full text |Cite
|
Sign up to set email alerts
|

Perforated gastric ulcer as the initial manifestation of hyperparathyroidism

Abstract: Primary hyperparathyroidism is characterised by autonomous production of parathyroid hormone resulting in hypercalcaemia. It is estimated that 12% of these patients present with peptic ulcer-related symptoms. The pathophysiological mechanism is not well established, but studies reveal serum calcium activating gastrin cell calcium receptors ultimately resulting in increased gastric acid production leading to peptic ulcer disease. A patient presented acutely to our service with peptic ulcer perforation in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…A rare but clinically important manifestation of hypercalcemia is the development of a PUD. It is reported that up to 12% of patients with primary hyperparathyroidism have peptic ulcer-related symptoms [ 12 , 16 , 17 ]. The mechanism of how hypercalcemia leads to PUD is not well established, but several studies back the notion that excess calcium activates the stomach calcium-sensing receptor located on the basolateral membrane of gastric parietal cells, which in turn increases gastric acid secretion [ 12 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A rare but clinically important manifestation of hypercalcemia is the development of a PUD. It is reported that up to 12% of patients with primary hyperparathyroidism have peptic ulcer-related symptoms [ 12 , 16 , 17 ]. The mechanism of how hypercalcemia leads to PUD is not well established, but several studies back the notion that excess calcium activates the stomach calcium-sensing receptor located on the basolateral membrane of gastric parietal cells, which in turn increases gastric acid secretion [ 12 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over time, persistent hypercalcemia can contribute to kidney damage and decreased kidney function [ 94 ]. In the digestive system, excessive calcium can cause constipation and, in some cases, might contribute to the development of stomach ulcers or gallstones [ 95 ]. Neurologically, high calcium levels can result in fatigue, lethargy, and, in severe cases, confusion or even coma [ 96 , 97 ].…”
Section: Essential Metals In Foodmentioning
confidence: 99%
“…В связи с тем, что достоверно не установлена взаимосвязь между двумя данными заболеваниями, неясен и возможный патогенез формирования язв желудка и двенадцатиперстной кишки при гиперпаратиреозе. Предположительно, основным звеном является повышение уровня кальция, что активирует продукцию гастрина и, в свою очередь, приводит к формированию язв желудка и двенадцатиперстной кишки [26].…”
Section: околощитовидные железыunclassified